PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS YANG DIMEDIASI OLEH KEPUASAN NASABAH PADA PT. BANK MUAMALAT INDONESIA CABANG DARMO SURABAYA - SATYA EDWARD SUBAGYO (Jurnal Manajerial, 2019)
This research examines the importance of customer satisfaction at PT. Bank Muamalat is influenced by employee services and employee loyalty, so far customer satisfaction is seen as a vital thing to be able to increase the company's income margin, therefore the company is very concerned about the variables that affect employee satisfaction, this study uses causal research using PLS program units and SPSS and using the sobel test, the results of this study are loyalty influencing satisfaction and satisfaction affecting and mediating services to customer satisfaction.